2014
DOI: 10.1039/c3dt53334d
|View full text |Cite
|
Sign up to set email alerts
|

Neutral copper(i) dipyrrin complexes and their use as sensitizers in dye-sensitized solar cells

Abstract: Heteroleptic neutral copper(I) dipyrrin complexes have been synthesised with the general formula [Cu(4,4'-(R)-6,6'-(CH3)-bipyridine)(dipyrrin)], R = CH3 or CO2Et, and H-dipyrrin is either 1,3,7,9-tetramethyldipyrromethene (HL1), 1,13-diphenyl-6,8-diisoindolemethene (HL2), or 1,13-diphenyl-3,11-di(trifluoromethyl)-6,8-diisoindolemethene (HL3). Improved stability was observed across the series , likely due to better steric constraints between the ligands. Visible light absorption has also been enhanced with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Further investigations by Constable [8e11] and Robertson [12] confirmed that Cu(I)-based complexes could be potentially efficient sensitizers coupled with mesoporous TiO 2 electrode in DSSCs [13]. Cu(I)-coordinated complexes, as sensitizers, exhibit prominent photophysical and photochemical properties [14e16], including the long-lived metal-to-ligand charge transfer (MLCT) excited states due to the d 10 configuration [17], broad MLCT transition bands in the visible region [13e18], and the potent reductant for the thermally equilibrated MLCT state [19].…”
Section: Introductionmentioning
confidence: 90%
“…Further investigations by Constable [8e11] and Robertson [12] confirmed that Cu(I)-based complexes could be potentially efficient sensitizers coupled with mesoporous TiO 2 electrode in DSSCs [13]. Cu(I)-coordinated complexes, as sensitizers, exhibit prominent photophysical and photochemical properties [14e16], including the long-lived metal-to-ligand charge transfer (MLCT) excited states due to the d 10 configuration [17], broad MLCT transition bands in the visible region [13e18], and the potent reductant for the thermally equilibrated MLCT state [19].…”
Section: Introductionmentioning
confidence: 90%
“…enhancement of performance with time) [5,25,28] and we routinely assess how the performance of a dye changes over days or weeks after fabricating the DSC.…”
Section: Synthesis and Characterization Of [Cu(2) 2 ][Pf 6 ]mentioning
confidence: 99%
“…We and others are focusing both our experimental and theoretical attention on dyes in which the chromophore is a copper(I) complex [4,5,6,7,8,9,10] Copper(I) diimine complexes are labile and the rapid ligand exchange processes [ 11 ] predicate against the isolation of chemically pure heteroleptic complexes, making this a challenging goal [12]. The recognition of this lability allowed us to develop a method of assembling TiO 2 -bound heteroleptic [Cu(L anchor )(L ancillary )] + dyes directly on a surface [4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize atom efficiency and to facilitate the screening of libraries of surface-bound dyes, we have developed methods of stepwise assembly of surface-bound bis(diimine) copper(I) dyes. In a further extention of the 'complexes-asligands' methodology introduced by the Bologna group for the systematic and regiospecific synthesis of homo-and heterometallic complexes [19,20], we have developed a powerful 'surfaces-as-ligands, surfaces-as-complexes' strategy for the preparation of DSSCs and other interfacial heterojunction devices [21,22,23,24,25,26,27,28]. In this approach, a nanoparticulate TiO 2 surface is treated with an anchoring ligand (L anchor ) which possesses two orthogonal functionalities: one is the anchoring group which interacts with the semiconductor (metal oxide in our case) surface and the other is one that can bind a metal centre.…”
Section: Introductionmentioning
confidence: 99%